Asymmetric Hetero-Diels–Alder Reaction of 4-Phenyl-1,2,4-triazole-3,5-dione with 2,4-Dienyl Carboxylic Acids - Sato, Yu; Ukei, Takahiro; Tsugeno, Hiromasa; Suga, Takuya; Soeta, Takahiro; Ukaji, Yutaka (Synthesis, 2023)
The enantioselective hetero-Diels–Alder reaction of the cyclic azo compound 4-phenyl-1,2,4-triazole-3,5-dione with 2,4-dienyl carboxylic acids was performed using tartaric acid ester as the chiral auxiliary. The corresponding cycloadducts were obtained with enantioselectivities of up to 76% ee. The cis-carboxylic acid produced could be converted into the corresponding cis- and trans-methyl esters by varying the reaction conditions.
Keywords: hetero-Diels–Alder reaction; 4-phenyl-1,2,4-triazole-3,5-dione; 2,4-dienyl carboxylic acid; tartaric acid ester; dehydropiperazine; methyl esterification